Activated PI3 Kinase Delta Syndrome: From Genetics to Therapy - Michalovich, David; Nejentsev, Sergey (Frontiers in Immunology, 2018)
Activated PI3 kinase Delta syndrome (APDS) is a primary immunodeficiency caused by dominant mutations that increase activity of phosphoinositide-3-kinase delta (PI3Kd). APDS can be caused by mutations in the PIK3CD gene that encodes PI3Kd catalytic subunit p110d (APDS1) or mutations in the PIK3R1 gene that encodes regulatory subunit p85a (APDS2). APDS research advanced rapidly after the initial discovery in 2013. More than 200 APDS patients have been identified around the world. Multiple novel APDS mutations were reported and molecular mechanisms leading to PI3Kd activation have been elucidated. The finding of APDS significantly increased our understanding of the role of PI3Kd in the human immune system. Perhaps most importantly, discovery of the molecular basis of this primary immunodeficiency suggested that APDS patients, who previously received only non-specific therapy, could be treated by a novel class of drugs that inhibits PI3Kd activity. This led to the ongoing clinical trials of selective PI3Kd inhibitors in APDS patients. Overall, the APDS story provides an excellent example of translational research, beginning with patients who had an unknown disease cause and leading to a novel specific knowledge-based treatment.